Nanobubbles for Precision Oncology - Dito Anurogo; Khadijah Zumratul Rabbani; Pudjo Dwi Laksono Dwi Laksono (PT Dexa Medica, 2026)
Nanobubbles (NBs) represent a unique class of sub-200 nm carriers that integrate deep tissue penetration with ultrasound (US)-responsive functionality, offering opportunities for simultaneous imaging, oxygenation, and therapeutic delivery in solid tumors. This review synthesizes the physicochemical principles governing NB stability with translational designconsiderations, including interfacial charge, free-lipid content, bubble spacing, and zeta (ζ)-potential as determinants of uptake and cytotoxicity. Particular emphasis is placed on gas-based payloads: oxygen nanobubbles for alleviating tumor hypoxia and carbon monoxide-releasing molecules (CO-RMs), nitric oxide (NO), and hydrogen sulfide (H₂S) for redoximmunometabolicmodulation within hormetic dose windows. Preclinical data demonstrate that oxygen nanobubbles enhance radiotherapy and chemotherapy responses by reversing hypoxia-induced resistance, while CO, NO, and H₂Sdonors—delivered in biphasic, dose-sensitive ranges—enable immunomodulation and reprogramming of the tumor microenvironment. We further distill case-level evidence (e.g., IR780–docetaxel nanobubbles in pancreatic cancer) intopractical design rules and discuss engineering levers such as shell composition, crosslinking chemistry, and acoustic parameterization. Finally, this review outlines translational roadmaps covering scalable manufacturing, imaging-guideddosimetry, and early-phase clinical strategies. Collectively, nanobubble-based, gas-augmented, ultrasound (US)-triggered systems represent an emerging precision platform with the potential to transition from experimental prototypes towardcontrolled clinical evaluation in oncology.